Treatment of Diabetic Ulcers with Mindi Leaf Hydrogel (Melia Azedarach L) to Reduce the Number of Bacteria - Noviana, Ineke; Mardiyono; Yosephina E. S. Gunawan; Umbu Putal Abselian; Ayu Wahyuni Lestari (JURNAL KESEHATAN PRIMER, 2025)
Background: Ulcers are one of the complications of Diabetes Mellitus. Modern society prefers non-pharmacological nursing procedures that are far from chemicals and are more traditional with natural ingredients and affordable prices and researchers found that mindi leaves with ingredients that can be used as anti-inflammatory, anti-diabetic and anti-bacterial are used to treat diabetic ulcers which are packaged in in hydrogel as a basic ingredient for modern treatments (modern dressings) at a dose of 270 mg to reduce the number of bacterial colonies in grade II diabetic ulcer patients. Objective: To determine the effectiveness of Melia Azedarach L hydrogel in reducing the number of bacterial colonies in sufferers of grade II diabetic ulcers. Method: Experiment with a sample size of 40 respondents through stratified random sampling and using the General Linear Model effectiveness test. Results: Mindi leaf hydrogel significantly reduced the number of bacterial colonies in patients with grade II diabetic ulcers with a value of p = 0.036. Conclusion: Treatment of diabetic ulcers with mindi leaf hydrogel is effective in reducing the number of bacterial colonies with a p value = 0.036.